1998
DOI: 10.1038/bjc.1998.36
|View full text |Cite
|
Sign up to set email alerts
|

Bryostatin 1-tamoxifen combinations show synergistic effects on the inhibition of growth of P388 cells in vitro

Abstract: Summary This study shows that combinations of bryostatin 1, a novel modulator of protein kinase C currently under clinical evaluation, with the anti-oestrogenic agent tamoxifen caused a large synergistic enhancement of growth inhibition in P388 cells in vitro. The growth-inhibitory effects of bryostatin 1 in the presence of non-inhibitory concentrations of tamoxifen were increased by approximately 200-fold, whereas growth inhibition by tamoxifen in the presence of non-inhibitory concentrations of bryostatin 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…A previous study has shown a large increase in PKC activity was observed after sequential treatment with non-toxic levels of bryostatin (a PKC activator) followed by TAM. 42 Consistent with this result, our previous study revealed that PB is a PKC activator. 43 It is likely that treatment with PB followed by TAM results in difference in activation, inhibition and intracellular translocation of individual PKC isoforms.…”
Section: Discussionsupporting
confidence: 81%
“…A previous study has shown a large increase in PKC activity was observed after sequential treatment with non-toxic levels of bryostatin (a PKC activator) followed by TAM. 42 Consistent with this result, our previous study revealed that PB is a PKC activator. 43 It is likely that treatment with PB followed by TAM results in difference in activation, inhibition and intracellular translocation of individual PKC isoforms.…”
Section: Discussionsupporting
confidence: 81%
“…The combined antitumor, immunopotentiating, and hematopotentiating properties of bryostatin 1 made it a promising candidate for clinical trials, and the results from the Phase I study (which began in early 1991) have demonstrated that bryostatin 1 may be administered safely (muscle soreness was the dose-limiting toxicity) and can induce a tumor response with a wide range of tumors . More recent tests have shown that bryostatin may synergize with both tamoxifen (in vitro) and paclitaxel (in vivo), and future clinical trials will probably assess the use of these combination therapies. The U.S. National Cancer Institute has moved bryostatin into Phase II trials against non-Hodgkin's lymphoma, melanoma, and renal cancer …”
Section: Introductionmentioning
confidence: 99%
“…However, several phase II studies were disappointing in melanoma [ 197 ], colorectal cancer [ 198 ], and gastric carcinoma [ 199 ]. Moreover, bryostatin-1 has demonstrated significant chemosensitizing activity when combined with conventional therapeutics including arabinofuranosylcytosine [ 200 ], tamoxifen [ 201 ], fludarabine [ 202 ], taxol [ 203 ] in leukemia cells. Protection of PKC from being downregulated by the strong ligand, phorbol ester, led to the design of selective PKC-binding bryostatin analogues.…”
Section: Pkc θ As Target In Clinicmentioning
confidence: 99%